Knowledge, Reflection and Strategy - Mark Avery (ACHSM, 2022)
This first issue of the journal for 2022 brings a comprehensive range of contributions from a number of authors. Reflection is a critically important process and opportunity that contributes to the development of strategy. Creating future opportunity stems from reflection on the past and engagement with issues of the current time. Research provides granular understanding for this.